2017
DOI: 10.1136/bjsports-2016-097372.132
|View full text |Cite
|
Sign up to set email alerts
|

Ametropia, Visual Deficits and Motor Performance in School Sports

Abstract: BackgroundIn childhood/puberty essential physical and school developments take place. Poor eyesight in this phase represents a handicap, as is known. Concluding, the basic correlation between a good eyesight and a safe, successful engaging in sports activities, as well as a motor development are documented through numerous studies. A database concerning the topic “Ametropia in school and its consequences on motor abilities” does not yet exist.DesignAgainst this background a study at 17 elementary and 6 high sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
1
0
2
Order By: Relevance
“…30 % aller Sportler bzw. 20 % der Leistungssportler fehlsichtig sind [10,13]. In einer anderen Studie waren 16,4 % der Sportler fehlsichtig, aber nur ein Viertel der Spieler, die eine Sehkorrektur benötigen, nutzten diese auch tatsächlich [14].…”
Section: Visuelle Leistungen Von Leistungssportlern Im Vergleich Zu Nicht-/freizeitsportlernunclassified
See 1 more Smart Citation
“…30 % aller Sportler bzw. 20 % der Leistungssportler fehlsichtig sind [10,13]. In einer anderen Studie waren 16,4 % der Sportler fehlsichtig, aber nur ein Viertel der Spieler, die eine Sehkorrektur benötigen, nutzten diese auch tatsächlich [14].…”
Section: Visuelle Leistungen Von Leistungssportlern Im Vergleich Zu Nicht-/freizeitsportlernunclassified
“…4 [10]. Auch im Spitzensport gibt es eine hohe Zahl an Fehlsichtigen, die ihren Sport ohne Sehhilfe ausüben [13]. Daher sind regelmäßige Sehtests auch aus unfall-und verletzungsprophylaktischer Sicht dringend notwendig, um Defizite möglichst frühzeitig aufzeigen und optisch korrigieren zu können [5].…”
Section: Räumliches Sehenunclassified
“…The literature [14] focused on abstracting the predictive accuracy and efficiency of regular soccer and bowling on the spread of college soccer spots and found that betting line differential was more accurate as a predictor of the eventual college winner. The literature [15][16] mentioned the combined relationship between team strength of soccer teams, team reputation and their attendance at games. It is argued that for college soccer to achieve better economic results in college soccer games.…”
Section: Introductionmentioning
confidence: 99%